Enterprise and organizational modeling and simulation : 13th International Workshop, EOMAS 2017, Held at CAiSE 2017, Essen, Germany, June 12-13, 2017, Selected Papers /: 13th International Workshop, EOMAS 2017, Held at CAiSE 2017, Essen, Germany, June 12-13, 2017, Selected Papers. (2017) - Unknown
No abstract available